Genomic epidemiology of antifungal resistance in human and avian isolates of Candida albicans: a pilot study from the One Health perspective - Domán, Marianna; Kaszab, Eszter; Laczkó, Levente; Bali, Krisztina; Makrai, László; Kovács, Renátó; Majoros, László; Bányai, Krisztián (Frontiers in Veterinary Science, 2024)
Stress-induced genomic changes in Candida albicans contribute to the adaptation of this species to various environmental conditions. Variations of the genome composition of animal-origin C. albicans strains are largely unexplored and drug resistance or other selective pressures driving the evolution of these yeasts remained an intriguing question. Comparative genome analysis was carried out to uncover chromosomal aneuploidies and regions with loss of heterozygosity (LOH), two mechanisms that manage genome plasticity. We detected aneuploidy only in human isolates. Birdderived isolates showed LOH in genes commonly associated with antifungal drug resistance similar to human isolates. Our study suggests that environmental fungicide usage might exert selective pressure on C. albicans infecting animals, thus contributing to the spread of potentially resistant strains between different hosts.